Investigation of 1n-evaporation channel of Superheavy nuclei with Z=102-113 - Kaur, Gurjit (My University, 2014)
Synthesis of superheavy nuclei (SHN) is a long-standing important subject of nuclear physics. The new elements which are synthesised are extremely important because they are expected to have new properties which may address some unresolved issues related to nuclear dynamics. Now a day the synthesis of SHN is getting more and more challenging due to smaller production crosssection either for cold or for hot fusion-evaporation reactions. Thus the appropriate theoretical research of existing methods is needed for proper understanding of dynamical aspect of superheavy nuclei. Keeping this in mind, we studied the 1n-decay pattern of a number of heavy/superheavy nuclei using hot and cold optimum orientations within dynamical cluster decay model (DCM) by considering β2 – deformations. In the present work we discuss 1n decay channel using Pb and Bi targets for nuclei lying in the range Z=102-113 within energy range =10.61-28.9 MeV. In the decay of these nuclei various factors such as fragmentation potential (V), preformation probability (P0) and penetrability (P) are analysed by fitting the neck length parameter ΔR of the model. In addition to this we have also investigated the exclusive role of deformations for these nuclei. Finally the comparative analysis of sticking and non-sticking moment of inertia is carried out by inspecting respective fragmentation paths.
MSc-Physics-Dissertation
Keywords: Superheavy element; Hot fusion; Cold fusion; SPMS